Endovascular closure of thoracic aortic pseudoaneurysms: A combined device occlusion and coil embolization technique in patients unsuitable for surgery or stenting. Issue 7 (3rd May 2016) - Lyen, Stephen M.; Rodrigues, Jonathan C.L.; Manghat, Nathan E.; Hamilton, Mark C.K.; Turner, Mark
Abstract : Objectives: Our aim was to retrospectively evaluate non‐stent graft closure of ascending aortic pseudoaneurysms at our center over a 10‐year period, and describe a combined device occlusion and coil embolization technique. Background: Aortic pseudoaneurysms (APAs) are a rare complication post cardiothoracic surgery, but can have fatal complications. There is increasing use of percutaneous interventional techniques for occlusion of aortic pseudoaneurysms in patients who are considered unsuitable for surgery. Stent graft deployment may not be possible depending on the specific anatomy and pathology. Methods and Results: Retrospective evaluation of the catheter laboratory database was performed at our center and anonymized data was obtained for patients who had nonstent endovascular treatment of APAs. Twelve patients were identified with a mean age of 63 ± 16 years. Seven patients had the combined occlusion and embolization technique, only 1/7 (14.3%) died from complications related to APAs. Five patients had occlusion device only, 3/5 (60%) died of complications related to their APA. The mean survival for the patients who had a combination procedure was 33.2±.22.6 months (range, 1 − 60 months), compared to 2.7 ± 2.6 months with device closure only (note 2 patients had short follow up of <3 months). Conclusions: We evaluate non‐stent graft percutaneous closure of APAs in a high‐risk patient group and provide data on the use of a novel combined occlusion device and coil embolization technique. We feel this is a viable approach to APA closure in this population but this will require larger clinical studies in the future. © 2016 Wiley Periodicals, Inc.